On determining characteristic length scales in pressure gradient turbulent boundary layers - Vinuesa, Ricardo; Orlu, Ramis; Schlatter, Philipp (Journal of Physics: Conference Series, 2016)
In the present work we analyze three methods used to determine the edge of pressure gradient turbulent boundary layers: two based on composite profiles, the one by Chauhan et al. (Fluid Dyn. Res. 41:021401, 2009) and the one by Nickels (J. Fluid Mech. 521:217-239, 2004), and the other one based on the condition of vanishing mean velocity gradient. Additionally, a new method is introduced based on the diagnostic plot concept by Alfredsson et al. (Phys. Fluids 23:041702, 2011). The boundary layer developing over the suction side of a NACA4412 wing profile, extracted from a direct numerical simulation at Rec = 400,000, is used as the test case. We find that all the methods produce robust results with mild or moderate pressure gradients, but stronger pressure gradients (with β larger than around 7) lead to inconsistent results in all the techniques except the diagnostic plot. This method also has the advantage of providing an objective way of defining the point where the mean streamwise velocity is 99% of the edge velocity, and shows consistent results in a wide range of pressure gradient conditions, as well as flow histories. Therefore, the technique based on the diagnostic plot is a robust method to determine the boundary layer thickness (equivalent to δ99) and edge velocity in pressure gradient turbulent boundary layers.
CRIS-Team Scopus Importer:2023-03-21